Germination Stage Screening of Mutants of Cowpea (Vigna unguiculata L. Walp) to Salinity Tolerance - Ndeye Fatou Deme; Mouhamadou Moussa Diangar; Mohd Yusuf Rafii; Mame Arama Fall-Ndiaye; Tahir Abdoulaye Diop (European Scientific Journal, ESJ, 2022)
To test the tolerance of cowpea mutants to salinity, cowpea wilds and mutants were subjected to 50, 100, 150, 200, and 250 mM NaCl to test for tolerance to salinity. Genotype and salt concentration interaction were significant. GxS explained mostly the variation observed. More informative salt concentrations were found in 50 mM (99.08) and C100 mM (72.50) against 26.80 in the control environment. High salt concentrations had the lowest germination rates. Seed germination rate of cowpea genotypes decreased from 56.46 to 20.58 with a mean of 36.28 and a variance of 99.08. Despite strong correlations observed between indices, very weak ones were found between AD and STI, -0.02, -0.44, -0.7, -0.79 and -0.84 respectively at salt concentration of 50, 100, 150, 200 and 250. Mouride wild types were most tolerant to salt with a germination rate of 43 % at 50 mM versus 48 and 551 % for respectively Melakh and Yacine. Six (6) mutants were more tolerant to the weakest checks performance which was the 9th best performance.